Use of special preparatory exercises for mastering the basic elements of sports acrobatics by young athletes 7-9 years old - Tetiana Chernykh; Viacheslav Mulyk; Tetiana Skaliy; Daria Okun (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to develop complexes of special preparatory exercises and determine the effectiveness of their use in mastering basic exercises for beginners acrobats. Material and methods: research was carried out on the basis of the Complex Children's Sports School No. 6, Slobodsky District (Kharkov). The study involved 28 children 6-7 years old, engaged in sports acrobatics in sports and health groups. The control group (n = 14) conducted the training process according to the CYSS program, experimental (n = 14) with the use of special exercises for each basic element ("swallow", "standing on the shoulder blades", "birch", "forward roll", "wheel"."bridging"), in the preparatory part of the lesson. At the end of the annual training, control testing of the implementation of the basic elements of young acrobats of 6-7 years old of the studied groups was carried out, which was assessed by 5 experts according to a 10-point assessment of their implementation. Results: in the process of using complexes of special exercises for each basic element of young acrobats 6-7 years old, reliably better assessment results were obtained in relation to the control group in performing exercises "swallow" (t = 6.25; p<0,001), "standing on the shoulder blades" (t=7,89; p<0,001), "forward roll" (t=4,00; p<0,001), "wheel" (t=4,69; p<0,001) and "bridging" (t = 4,33; p <0,001). Conclusions: as a result of the research, it was found that the use of the developed complexes of special exercises for mastering the basic elements by young acrobats of 6-7 years old effectively influences the formation of the elements of the technique of basic exercises and psychophysiological indicators, ensures their implementation.